2019
DOI: 10.1094/pdis-05-18-0879-re
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Analysis of Phytophthora parasitica From Tobacco in Chongqing, Southwestern China

Abstract: Tobacco black shank, caused by Phytophthora parasitica, is one of the most notorious tobacco diseases and causes huge economic losses worldwide. Understanding the genetic variation of P. parasitica populations is essential to the development of disease control measures. In this research, 210 simple sequence repeat (SSR) markers for P. parasitica were identified, 10 of which were polymorphic among nine reference strains. We further performed population genetic analysis of 245 P. parasitica isolates randomly col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…N. benthamiana seeds were sown on soil in a matrix and cultured in a Phytotron with a 13 hr light:11 hr dark photoperiod for about 30–40 days. P. parasitica strains were routinely maintained on 5% carrot agar (CA) plates (Zhang et al , ). Incubation conditions were as follows: 23 °C, darkness.…”
Section: Methodsmentioning
confidence: 99%
“…N. benthamiana seeds were sown on soil in a matrix and cultured in a Phytotron with a 13 hr light:11 hr dark photoperiod for about 30–40 days. P. parasitica strains were routinely maintained on 5% carrot agar (CA) plates (Zhang et al , ). Incubation conditions were as follows: 23 °C, darkness.…”
Section: Methodsmentioning
confidence: 99%
“…These reports are also in line with another study that revealed a low population genetic diversity of P. parasitica in Chongqing resulting from clonality, as there is only MT A2 reported in the population. The limited population variation in this population is most likely from random mutation [48]. The occurrence of sexual reproduction in a population does not always result in genetic recombination.…”
Section: Mode Of Reproductionmentioning
confidence: 99%
“…There are many important biological features attributed to SSRs such as codominance, multiallelic nature, and genetic markers just to name a few. These features are used for determining the mating type, genome reconstruction, disease dynamics, and determination of population structures ( Schena et al, 2008 ; Biasi et al, 2016 ; Stewart et al, 2016 ; Engelbrecht et al, 2017 ; Parada-Rojas and Quesada-Ocampo, 2018 ; Hieno et al, 2019 ; Zhang et al, 2019 ; Guo et al, 2021 ). The available literature indicates studies involving fewer species and lacks a broader view.…”
Section: Introductionmentioning
confidence: 99%